PEMODELAN MATEMATIK SISTEM HIDROLIK PADA MAIN LANDING GEAR EXTENSION DAN RETRACTION PESAWAT BOEING 737-900ER DENGAN PROGRAM MATLAB-SIMULINK - Mohammad Ardi Cahyono; Rahmat Suwandi (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
The problem that often arises in the hydraulic system when the main landing gear is done extension and retraction is the control o f the hydraulic motion and the fluid motion is very big influence on the hydraulic work process where the fluid flow must be ensured or arranged in such a way as to work properly. To overcome this problem, a mathematical modeling system is used to create a representation or an imitation o f the actual system, which links the output o f the system with its input in a mathematical relationship and its parameter values. The research was conducted by observation method and literature study to obtain the data and its calculation. The results o f this study obtained a description o f the response and dynamic characteristics o f the PID controller in the transfer function o f the hydraulic system when the main landing gear extension and retraction o f the nearest Boeing 737-900ER aircraft is the 5th time experiment by inputting PID controller value P = 13 I = 4 D = 3 with an error value o f 0.01887 and an overshoot o f1,0002. With a small error value or a 2% value limit and the response picture is not experiencing a large overshoot, then the picture o f the response in accordance with the expected in the 5th experiment where the error value o f 0.01887 and overshoot o f 1,0002. With an overview o f the response with this small overshoot then the accuracy o f the system will stop at the point corresponding to the actual system. By using this modeling, the response o f the main landing gear extension and retraction movements can be well studied thus providing a good understanding o f the performance of the hydraulic system.